THE INFLUENCE OF VITAMIN AND MINERAL COMPLEX ON MILK PRODUCTION AND HEMATOLOGIC INDICATORS OF COWS - Dovhiy, Yu. Yu.; Senichenko, V. Yu.; Feshchenko, D. V.; Chala, I. V. (Scientific Progress & Innovations, 2019)
Using feed supplements of the natural and artificial origin in the ration of cattle is a common and effective way to raise animal productivity and improve their health. The opportunity to enrich the rations of milking cows with vitamins and minerals available to most national owners deserves particular attention. The purpose of this scientific work was researching the impact of the complex of vitamins, macro- and microelements on milk productivity, morphological and biochemical indices of cows’ blood. The novelty of the research is using the vitamin preparation “Solvimin Selen” together with the complex of mineral microelements which provides the activation of the main metabolic routes of lactating cows under the conditions of intensive framing. Two cow groups were created: the control and experimental ones based on the principle of analogues. Blood was taken from 5 cows of each group for laboratory testing on the 1st, 30th and 90th day of the experiment. Cows of the control group were held on typical nutrition, while special trace element salts (copper sulfate, zinc sulfate, cobalt chloride, potassium iodide) were added to the ration of the experimental cow group together with the preparation “Solvimin Selen” in the amount of 6 gram per cow during 7 days. On the 90th day of the experiment it resulted in increasing milk productivity by 18.1 % and improving the morphological indices of cow blood (the number of erythrocytes, leukocytes, segmental-nuclear neutrophils), which was the evidence of stimulating hematopoiesis and the factors of nonspecific immunity. The changes in biochemical blood indices of cows, especially on the 90th day after adding vitamin-mineral supplements in the ration, testified to the improved regulation of protein, lipid and carbohydrate metabolism chains. In particular, the raising of such indices, as total protein, albumin, total bilirubin, urea, total carotene, inorganic phosphorus, aspartate transaminase, cholesterol, and glucose was noticed. Such indices as kreatinine, globulin didn’t change much. Everyday using of vitamins and minerals in cows’ feeds during 30 days allowed to maintain the clinical condition of animals, resume the physiological course of metabolic processes in the body of animals and increase milk productivity. The using of vitamin- mineral supplement also contributed to the stabilization of the digestive system and prevented the hypotension of the rumen.